Decreased physical activity is a predictor for a complicated recovery post cardiac surgery. Issue 1 (January 2017) - van Laar, Charlotte; TImman, Simone; Noyez, Luc
Abstract Background Physical activity (PA) reduces the risk of cardiovascular disease and physically active survivors of a cardiac event are at lower risk of recurrent events. We hypothesized that patients with a decreased PA, undergoing cardiac surgery, are at higher risk for a postoperative complicated recovery (PCR). Methods Three thousand three hundred eighty two patients undergoing elective cardiac surgery between January 2007 and December 2013 were included. The group was divided into three subgroups: group A, aged ≤ 65 years (N  = 1329); group B, aged > 65 years and ≤ 75 years (N  = 1250); and group C aged >75 years (N  = 803). To assess PA, the criteria of the Corpus Christy Heart Project were used. A PCR consists of the occurrence of a major postoperative event, defined as any of the following complications: reoperation, deep sternal wound infection, renal failure, stroke, postoperative ventilation > 2 days, intensive care stay ≥ 5 days, hospital stay ≥ 10 days, or hospital mortality. Results One thousand three hundred sixty seven patients (40%) were considered as patients with a decreased PA. Both in group B (p  = 0.001) and in group C (p  = 0.003), patients with a decreased PA were significantly associated with an increased risk of a PCR, which was not the case in group A (p  = 0.28). Logistic regression analysis identified a decreased PA as an independent predictor for PCR in groups B (p  = 0.003, odds 1.71) and C (p  = 0.033, odds 1.48), but not in group A (p  = 0.11, odds 0.71). Conclusion Decreased physical activity is an independent predictor for a PCR in patients aged 65 years or older undergoing elective cardiac surgery.